PENGGUNAAN BEKISTING BONDEK UNTUK PERCEPATAN WAKTU PROYEK BANGUNAN BERTINGKAT 26 LANTAI - Rachmi Yanita; Terry Novi AR (Racic : Rab Construction Research, 2022)
Abstract Conventional formwork using multiplex material and bondek formwork are types of formwork that have their respective advantages. The choice of formwork type is determined by the project constraints of each project. For time and cost optimization, value engineering was carried out between the two formwork methods in planning the construction of the 26-storey Urban Height Residences Apartment Project with a floor area of ​​10,000 m2 in South Tangerang. Implementation of typical slab and beam structure work, divided into 2 work zones for work effectiveness. In conventional formwork, the need for formwork material is based on the cycle of formwork transfer between zones and between floors, so it is sufficient to use formwork with an area of ​​4 floors and above is carried out with conventional formwork and bonded formwork. In the time analysis, an analysis of the time requirements is made for the process of installing, dismantling and removing formwork. From the results of the analysis obtained that the conventional formwork multiplex (plywood) requires a cost of Rp. 2,168,573,650,- for a typical floor area of ​​35,974.75 m2, or Rp. 60,280,-/m2 which is 64.36% more effective than using bondek formwork. In terms of time, conventional multiplex (plywood) formwork takes 250 days to work, with a daily productivity of 143,899 m2/day, 20% longer than bondek formwork. The type of formwork used in the design stage must be in accordance with the project constraints so as to produce an optimal design. Keywords: Conventional Formwork, Bondek Formwork, Project Constraint.